Social influences towards conformism in economic experiments - Shaun P. Hargreaves Heap (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
This paper reviews some of the economic experimental evidence on conformism. There is nothing to match the early psychology experiments where subjects were often swayed by the behaviour of others to an extraordinary degree, but there is plenty of evidence of conformism. This seems built-in to our sociality either because we have preferences for conversation or status which are activated by the knowledge of what others do, or because other people face relevantly similar decisions to our own and so that their behaviour signals something useful to us about the uncertain world. These social influences can cause mischief. The more worrying cases, however, are those where individual preferences themselves change through interaction with others: the strongest experimental evidence for this is with respect to individual social preferences, particularly in a context where individuals belong to different groups.
Keywords: C91; C92; D43; H41; 330; Conformism; cascade; social comparison; social preferences; in-group bias